Stylistic Analysis on Smile You Nutter! By Darren Hobson - Diani Syahputri; Yusni Khairul Amri; Leli Roswinda (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
The study aimed to analyze Darren Hobson’s poetry “Laugh You Nutter” from the view of stylistic analysis. It seen through the aspects of morphological level which about the word forms appeared in the poetry based on the kinds of morphology stylistics such unbound (free morphemes), bound (inflectional and derivational morphemes), base and cranberry morphemes. The poet exhibits a madness experience that could encourage the readers’ feeling. This research used descriptive qualitative approach. This paper is useful in revealing the words style of language and the meaning of the poem. Based on them, it implies that the students could learn English linguistics and literature widely by absorbing the subject about stylistic and poetry.